Formation of Silicon Carbide Films by Magnetron Sputtering of Compound Carbon-silicon Target - V.I. Perekrestov; A.S. Kornyushchenko; I.V. Zahaiko (Журнал нано- та електронної фізики)
In the proposed work conventional methods of SiC layers formation and polytypes of this compound have been reviewed. A new methodology of silicon carbide obtaining has been proposed. It is based on magnetron sputtering of compound targets. The optimal geometrical characteristics of the compound targets made of silicon and graphite have been calculated. The condensates structure and composition were studied with help of transmission electron microscopy (TEM), electron diffraction along with the energy dispersive X-ray elemental analysis. On the basis of the investigations the geometrical characteristics of the compound target and the optimal technological parameters required for the formation of silicon carbide in the form of 3С-SiC polytype with element composition close to stoichiometric have been determined.